Promoting Intercultural Competences and Communication Skills through English Textbooks within Multilingual Education: Intercultural Language Learning; English Textbooks - Haerazi Haerazi; Jayrome Lleva Nunez (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2021)
In intercultural and transcultural communication contexts within multilingual education, English learners should be able to communicate and interact with other people who have different linguistic and cultural background. For this reason, intercultural contents should be incorporated in EFL textbooks to promote learners’ intercultural competences and communication skills. The contents are designed with containing not only Anglo-American and British cultural dimensions but also learners’ home and foreign cultures. It is to prepare learners to become global citizens. The principal aim of this study is to investigate how teachers apply English textbooks to promote learners’ intercultural competences and intercultural communicative skills within multilingual education. This article argues that intercultural representations incorporated in EFL textbooks are used as useful resources for helping learners develop their intercultural competences and communication skills. also, the ways teachers carry out their teaching in the classes are measured. The results of this study show that the teachers employ EFL textbooks effectively with utilizing potential teaching materials containing cultural values to promote learners’ intercultural competences and communicative skills within multilingual education. This study also suggests that English teachers needs reinforcement in multilingual education.